2006
DOI: 10.1007/s00421-006-0227-4
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged exercise does not cause lymphocyte DNA damage or increased apoptosis in well-trained endurance athletes

Abstract: Recent research has demonstrated that lymphocyte apoptosis sensitivity appears to be related to training status and exercise intensity. This work investigated the effect of prolonged, submaximal treadmill running on percentage (%) apoptosis, % necrosis and DNA strand breaks in lymphocytes and related these to changes in total lymphocyte and blood cortisol concentrations in well-trained runners. Venous blood samples (n = 14) were taken immediately before (PRE), immediately after (IPE) and 3 h after (3PE) 2.5 h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
1
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 28 publications
(47 reference statements)
1
33
1
4
Order By: Relevance
“…In contrast, Peters et al [2006] found no significant increases in DNA migration as a measure of damage at 3 h post-exercise following 2.5-h exercise trials. Moreover, Mars et al [1998] described significant increases in both DNA strand breaks and apoptotic cells in untrained subjects, immediately after incremental exercise protocol to exhaustion, but not 24 and 48 hours after exercise.…”
Section: Muscle 8-ohdg Levelscontrasting
confidence: 59%
See 1 more Smart Citation
“…In contrast, Peters et al [2006] found no significant increases in DNA migration as a measure of damage at 3 h post-exercise following 2.5-h exercise trials. Moreover, Mars et al [1998] described significant increases in both DNA strand breaks and apoptotic cells in untrained subjects, immediately after incremental exercise protocol to exhaustion, but not 24 and 48 hours after exercise.…”
Section: Muscle 8-ohdg Levelscontrasting
confidence: 59%
“…This is supported by the fact that in endurance-trained individuals, the Type I fibers are more noticeable because of abundant mitochondrial density compared with the Type II fibers [Coyle 1995]. Thus, trained athletes or individuals who are regularly involved in endurance training may have an enhanced adaptive response, which results in a protective effect against oxidative stress [Radak et al 2003] and attenuates the extent of apoptosis (e.g., DNA fragmentation and caspases activity) [Peters et al 2006]. However, whether or not DNA damage directly results from oxidative damage, or whether it is derived from a part of the process of apoptosis remains elusive [Mars et al 1998].…”
Section: Muscle 8-ohdg Levelsmentioning
confidence: 99%
“…Apoptosis is a programmed cell death process that takes places in different cells during both embryonic and adult life (23). Exercise can either cause (24), inhibit (25) or have no effect on apoptosis of different cell types (26). The probable mechanisms responsible for exercise -induced apoptosis include: increased glucocorticoid hormone, intracellular calcium concentration and reactive oxygen species (27).…”
Section: Discussionmentioning
confidence: 99%
“…However, as more researchers began to investigate the ability of exercise to serve as a stimulus to induce apoptosis in lymphocytes, some authors began to question these findings, particularly in terms of its role in the post-exercise decrease in immune cell volume, termed lymphocytopenia [6,7]. In fact, two opposing views began to form: that exercise is capable of inducing lymphocyte apoptosis and does contribute to lymphocytopenia; and that exercise does not induce apoptosis and therefore plays no role in the decrease in circulating lymphocyte concentration observed following exercise.…”
mentioning
confidence: 99%